2019
DOI: 10.1136/injuryprev-2019-043225
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the drowning mortality rate in Iran

Abstract: ObjectiveThe WHO estimates the global incidence of death by drowning to be about 300 000 cases per year. The objective of this study was to estimate the trend in mortality due to drowning in all provinces of Iran in all age groups and both genders from 1990 to 2015.Study designThe National and Subnational Burden of Diseases (NASBOD) project is a comprehensive project in Iran. It is based on the Global Burden of Disease study and includes novel methods to estimate the burden of diseases in Iran.MethodsThis stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…There were a further 11 studies [ 35 , 40 , 43 , 44 , 50 , 52 , 54 – 56 , 83 , 93 ] which reported fatal drowning rates by sex and/or age group, the majority of these studies came from Iran. When exploring the EMR as a whole, data from 2004 for children and adolescents aged 0–19 years indicated the highest fatal drowning rate among 1–4 year-olds (9.0 / 100,000 population).…”
Section: Resultsmentioning
confidence: 99%
“…There were a further 11 studies [ 35 , 40 , 43 , 44 , 50 , 52 , 54 – 56 , 83 , 93 ] which reported fatal drowning rates by sex and/or age group, the majority of these studies came from Iran. When exploring the EMR as a whole, data from 2004 for children and adolescents aged 0–19 years indicated the highest fatal drowning rate among 1–4 year-olds (9.0 / 100,000 population).…”
Section: Resultsmentioning
confidence: 99%
“…Similar findings are reported in 33 European countries [ 119 ], and Australia [ 120 ]. The decrease, with rates that vary between 5 and 80%, is also reported in studies initiated in low and middle-income countries or based on the Global Burden of Disease registrations (GBD) [ 2 , 24 , 38 , 77 , 121 124 ]. This decreasing trend in accidental drowning is speculatively explained by better socioeconomic situations, improved infrastructure planning such as piped water supply resulting in less frequent and less easy access to water, mandatory education, safer swimming and bathing facilities, aquatic safety education and swimming lessons [ 10 , 22 , 24 , 125 – 127 ).…”
Section: Discussionmentioning
confidence: 66%
“…The results indicate that although the incidence of drowning is lower than the other injuries, but the mortality ratio in drowning is higher than other injuries. According to the Iranian Forensic Medicine Organization, from 2013 to 2017, 3716 deaths occurred due to drowning in Iran (Derakhshan et al, 2020), of which, about one third (1010 deaths) had happened in rivers. Unfortunately, most rivers do not have warning signs, many people do not realize how dangerous swimming can be, and due to nancial problems, they cannot enjoy the bene ts of swimming in private pools (Derakhshan et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…According to the Iranian Forensic Medicine Organization, from 2013 to 2017, 3716 deaths occurred due to drowning in Iran (Derakhshan et al, 2020), of which, about one third (1010 deaths) had happened in rivers. Unfortunately, most rivers do not have warning signs, many people do not realize how dangerous swimming can be, and due to nancial problems, they cannot enjoy the bene ts of swimming in private pools (Derakhshan et al, 2020). According to the results of the current study, the mortality rate from falling, tra c injuries, poisoning, burns and electrocution has been declining in recent years.…”
Section: Discussionmentioning
confidence: 99%